2022
DOI: 10.3389/fpls.2022.961692
|View full text |Cite
|
Sign up to set email alerts
|

Variation characteristics of different plant functional groups in alpine desert steppe of the Altun Mountains, northern Qinghai-Tibet Plateau

Abstract: In grassland ecosystems, the plant functional group (PFG) is an important bridge connecting individual plants to the community system. The grassland ecosystem is the main ecosystem type on the Qinghai-Tibet Plateau. Altun Mountain is located in the key grassland transcontinental belt of the northern Qinghai-Tibet Plateau. The composition and changes in the PFG in this ecosystem reflect the community characteristics in the arid and semi-arid extreme climate regions of the Plateau. The main PFGs were forbs and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, further research is needed to confirm this. Research conducted by Zhang et al, (2022) concerning the variations in the characteristics of different plant functional groups in the northern Qinghai-Tibet grasslands identified 22 species, which were divided into four groups according to their functional groups, namely forbs, grasses, legumes, and sedges. They found that grassland communities were dominated by forbs and grasses, which accounted for more than 50% of the importance value to the community.…”
Section: Functional Groups Of Herbaceous Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further research is needed to confirm this. Research conducted by Zhang et al, (2022) concerning the variations in the characteristics of different plant functional groups in the northern Qinghai-Tibet grasslands identified 22 species, which were divided into four groups according to their functional groups, namely forbs, grasses, legumes, and sedges. They found that grassland communities were dominated by forbs and grasses, which accounted for more than 50% of the importance value to the community.…”
Section: Functional Groups Of Herbaceous Plantsmentioning
confidence: 99%
“…In general, the percentage of forbs and grasses in the grasslands of West Timor was relatively higher compared to the grasslands of northern Qinghai-Tibet. According to Zhang et al, (2022), the grasslands of northern Qinghai-Tibet have a dry and cold climate, so the dominant community functional groups were grasses and forbs. This was mainly due to forbs having strong adaptability to dry environments and grasses having a conservative resource use strategy and being very cold tolerant, so grasses and forbs can adapt well to upland environments.…”
Section: Functional Groups Of Herbaceous Plantsmentioning
confidence: 99%
“…As a result, the large-scale desertification differentiation process in the semi-arid alpine highlands is a complex process combining multi-media participation and multi-level driving. Compared with the traditional studies on desertification in dry land habitats, desertification in semi-arid alpine ranges at numerous temporal and spatial scales is more intricate, distinctive, and unique [28,29]. It is surprising that the dynamics and underlying processes of desertification risk in semi-arid alpine highlands have received little attention to far.…”
Section: Introductionmentioning
confidence: 99%